Latin American Culture and the Limits of the Human - Merchant, Paul (Lecturer); Bollington, Lucy (Book collections on Project MUSE., 2020)
"This volume explores works from Latin American literary and visual culture that question what it means to be human and how the nonhuman world helps define personhood. In doing so, it provides new perspectives on how the region challenges and adds to global conversations about humanism and the posthuman"--